2020
DOI: 10.1186/s12876-020-01331-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of non Helicobacter pylori gastric Helicobacters in Iranian dyspeptic patients

Abstract: Background: Non Helicobacter pylori gastric Helicobacters (NHPGHs) are associated with a range of upper gastrointestinal symptoms, histologic and endoscopic findings. For the first time in Iran, we performed a crosssectional study in order to determine the prevalence of five species of NHPGHs in patients presenting with dyspepsia. Methods: The participants were divided into H. pylori-infected and NHPGH-infected groups, based on the rapid urease test, histological analysis of biopsies, and PCR assay of ureA, ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
8
1
Order By: Relevance
“…All of the 50 patients in this study were almost asymptomatic, and were incidentally diagnosed as NHPH infection by gastric biopsy in a regular checkup EGD. Some previous studies have reported that NHPH was detected with high proportions in symptomatic patients 11 , 13 , 14 . However, the result of our study shows that, also in NHPH‐infected patients, the proportion of asymptomatic patients is likely to be greater than that of symptomatic patients as well as in H .…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…All of the 50 patients in this study were almost asymptomatic, and were incidentally diagnosed as NHPH infection by gastric biopsy in a regular checkup EGD. Some previous studies have reported that NHPH was detected with high proportions in symptomatic patients 11 , 13 , 14 . However, the result of our study shows that, also in NHPH‐infected patients, the proportion of asymptomatic patients is likely to be greater than that of symptomatic patients as well as in H .…”
Section: Discussioncontrasting
confidence: 70%
“…Some previous studies have reported NHPH infection cases that had been asymptomatic and were unexpectedly found by EGD for regular health check 5,10 . On the other hand, NHPH is also reported to be associated with dyspeptic symptoms and parkinsonism 11–14 . Regarding MALT lymphoma, Stolte et al found it in 7 of 202 patients with NHPH gastritis, 15 and Okiyama et al found it in 4 of 15 patients with NHPH gastritis 16 …”
Section: Discussionmentioning
confidence: 99%
“…Two PCR assays were used for detection of H. pylori DNA, one targeting the ureAB gene and the other one targeting the glmM gene. Although a number of studies have been published diagnosing H. pylori infection based on a ureAB gene PCR only [ 19 , 37 , 38 ], some reports indeed claim that H. pylori identification should include these two different target genes amplification [ 39 41 ]. Lu et al compared five PCR methods for detection of H. pylori DNA of 24 culture-positive samples obtained from 50 human gastric samples, including PCRs targeting the ureA and glmM gene.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cases of bacteraemia of non- H. pylori Helicobacter species have been reported 483 484. Multiple non- H. pylori Helicobacter species have been linked with various gastric conditions in patient cohorts, case series or case reports including dyspepsia,485 gastritis,486 487 peptic ulcer disease,488 489 gastric cancer490 and gastric mucosa-associated lymphoid tissue lymphoma 491 492. In addition, numerous case reports have been published revealing associations with gastroenteritis 493 494.…”
Section: Wg 5: Helicobacter Pylori and The Gut Microbiotamentioning
confidence: 99%